IMPLEMENTASI AUGMENTED REALITY SEBAGAI MEDIA PENGENALAN SPAREPART MOBIL BERBASIS ANDROID - Sihombing, Joel; Simanjuntak, Pastima (Computer Science and Industrial Engineering, 2021)
Technology is something that cannot be separated from the mobility of life and has an important role and over time technology has experienced a wide expansion, for example in the development of software and so on. Augmented Reality is a technology that is developing at this time where the technology utilizes the sophistication of the features of a smartphone so that it can display objects from two dimensions into 3D. Car spareparts are components that have a very important function on the vehicle. The introduction of spareparts still utilizes two-dimensional images in the introduction process. Augmented Reality is a technology that is developing at this time where the technology utilizes the sophistication of the features possessed by smartphones so that it can display objects from two dimensions into 3D digitally based on the Android operating system. Augmented Reality applications are developed using the C# programming language on Unity Engine, using the Vuforia database and Blender. Marker is a marker like an image where when the smartphone camera is pointed at the marker it can display 3D objects. Augmented Reality applications can be used by users on smartphones, thus becoming a more attractive alternative means of introducing car spareparts.